2019
DOI: 10.1177/2167702619851808
|View full text |Cite
|
Sign up to set email alerts
|

Are Different Forms of Repetitive Negative Thinking Associated With Interpretation Bias in Generalized Anxiety Disorder and Depression?

Abstract: Worry and rumination, two forms of repetitive negative thinking (RNT), are prevalent in generalized anxiety disorder (GAD) and depression. Cognitive processing biases, especially the tendency to draw negative conclusions from ambiguous information (interpretation bias), may maintain worry and rumination. Yet the relationship between interpretation bias and both forms of RNT has not been explored in clinical versus nonclinical samples. In this cross-sectional study, participants with GAD ( n = 72), depression (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…If you have a negative interpretation bias, you might mistakenly imagine the audience is harboring harsh criticisms of your work and you must have done a poor job. Dysphoric individuals exhibit patterns of evaluating and assigning emotionally relevant meaning to ambiguous information in a manner that is decidedly negative (Lee et al, 2016) and do so to a higher degree than non-dysphoric persons (Everaert, Podina, et al, 2017; Krahe et al, 2019). It should be noted that these negative interpretation biases appear most pronounced when situations are directly relevant to oneself (Cowden Hindash & Rottenberg, 2017; Wisco, 2009; Wisco & Nolen-Hoeksema, 2010).…”
Section: Negative Interpretation Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…If you have a negative interpretation bias, you might mistakenly imagine the audience is harboring harsh criticisms of your work and you must have done a poor job. Dysphoric individuals exhibit patterns of evaluating and assigning emotionally relevant meaning to ambiguous information in a manner that is decidedly negative (Lee et al, 2016) and do so to a higher degree than non-dysphoric persons (Everaert, Podina, et al, 2017; Krahe et al, 2019). It should be noted that these negative interpretation biases appear most pronounced when situations are directly relevant to oneself (Cowden Hindash & Rottenberg, 2017; Wisco, 2009; Wisco & Nolen-Hoeksema, 2010).…”
Section: Negative Interpretation Biasmentioning
confidence: 99%
“…In fact, others have proposed this very idea and supporting evidence has been found. Rumination is significantly associated with negative cognitive styles (Krahé et al, 2019;Spasojevic & Alloy, 2001), and negative cognitive styles moderate the association between rumination and depression symptoms, such that this association is stronger as negative cognitive styles increase. Additionally, predictable changes in depressive symptoms have been observed via the processing of negative cognitive biases through rumination (Ciesla & Roberts, 2007).…”
Section: Rumination As a Mechanismmentioning
confidence: 99%
“…The groups did not differ in their rejection of threatening but impossible interpretations (foils), thus ruling out the effects of a general threat-based response bias. Using the same task, Krahé et al (48) further demonstrated that worry was associated with negative interpretation bias across the general population, and that participants with GAD were biased towards negative interpretations, while community volunteers were biased towards benign (i.e. neutral or positive) interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…In a cognitive model of pathological worry, proposed that worry arises in GAD due to a combination of factors, such as an automatic cognitive bias in which emotionally ambiguous events are interpreted as threatening. Supporting this hypothesis, Krahé et al (2019) demonstrated that worry is associated with a more negative interpretation bias, and evidence of a causal role for interpretation bias in the maintenance of worry and anxiety has been found in experiments using Cognitive Bias Modification (CBM). CBM for interpretation, pioneered by Grey and Mathews (2000) and Mathews and Mackintosh (2000), adapts paradigms designed to assess interpretation bias to train a certain -usually benign -interpretive style.…”
Section: Generalized Anxiety Disorder: a Randomized Controlled Experimentsmentioning
confidence: 83%